The synthesis of novel directly conjugated zinc(II) phthalocyanine via palladium-catalyzed Suzuki–Miyaura cross-coupling reaction and its quaternized water-soluble derivative: Investigation of photophysical and photochemical properties. (November 2016) - Yanık, Hülya; Al-Raqa, Shaya Y.; Aljuhani, Ateyatallah; Durmuş, Mahmut
Abstract: The novel zinc(II) phthalocyanine directly conjugated with 4-(diethylamino)phenyl groups (2 ) via CC bond formation using Suzuki-Miyaura coupling reaction was synthesized for the first time. This phthalocyanine was converted to the quaternized derivative (3 ) to enhance its water solubility. The photochemical (singlet oxygen quantum yield and photodegradation quantum yield) and photophysical (fluorescence quantum yield and lifetime) properties of the synthesized novel zinc(II) phthalocyanines (2 and3 ) were investigated in DMSO (for both phthalocyanines2 and3 ) and in aqueous solution (for only phthalocyanine3 ) for determination of their photodynamic therapy abilities. Additionally, the bovine serum albumin (BSA) binding behavior of the water soluble zinc(II) phthalocyanine (3 ) was investigated in aqueous solution for determination of transporting capability of this phthalocyanine in the circulatory system. Graphical abstract: The novel zinc(II) phthalocyanine directly conjugated with 4-(diethylamino)phenyl groups via CC bond formation using Suzuki-Miyaura coupling reaction was synthesized for the first time. This phthalocyanine was converted to the quaternized derivative to enhance water solubility and promising as photosensitizer for photodynamic therapy. Highlights: Directly 4-(diethylamino)phenyl conjugated zinc(II) phthalocyanine was synthesized. Suzuki-Miyaura coupling reaction was used for synthesis of this phthalocyanine. The photophysical and photochemical properties were investigated. This compound can promise as theranostic (treatment and diagnostic) agent for cancer.